PERANCANGAN AUDIO VISUAL PROMOSI CAFE KAPATOMAN, TARUKO-KABUPATEN AGAM - M Fadhli Al-Farisi, Ir. Drs. Heldi, M.si., Ph.D. Dr. M. Nasrul Kamal, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Cafe Kapatoman was founded by Anil Basya in 2018, having his address at Taruko, Ngarai Sianok, Agam Regency, West Sumatra Province. The absence of audio-visual promotion is very influential on the existence and image of its business, so it requires the design of promotional audio visuals in the form of videos with themes that represent the concept of the Kapatoman cafe. The purpose of this design is a manifestation of the author's desire that the Kapatoman cafe has promotional media in the form of audio visuals that aim to create informative and communicative information media, so that the existence of Kapatoman cafe can be known by the public.The design method of the Kapatoman cafe promotional audio visual is through descriptive qualitative methods using the 5w + 1h analysis method (What, Who, When, Where, Why, How) The orientation of developing this promotional audio visual design idea includes the main media in the form of promotional videos and supporting media in the form of T-shirts, promotional cars, mugs, xbanners, audio visual promotion this promotion can have promotional media in the form of audio visual which aims to create informative and communicative information media, so that the existence of Kapatoman cafe can be known by the public and the increase in sales of Kapatoman cafe sales.Keywords: Designing, Promotional Audio Visual, Cafe Kapatoman.